Do green foreign direct investments promote environmental innovation in European countries? - Nhuong, Bui Huy; Bao, Ho Dinh; Linh, Vu Manh; Ha, Le Thanh (Center of Biomass & Renewable Energy (CBIORE), 2025)
Environmental innovation (EI) plays a critical role in helping a country pursue sustainable development, while green foreign direct investment (GFDI) impacts creative local green innovation. However, there is a lack of research on this link. This paper aims to conduct an empirical investigation into how GFDI affects EI. The estimation findings demonstrate that GFDI has had positive effects on EI—by applying multiple econometric methods, including a panel-corrected standard error modelling (PCSE), a feasible generalized least squares model (FGLS), and autoregressive distributed lag (ARDL) model, to a globally representative sample of 15 European countries between 2012 and 2021. To clarify the connection between GFDI and EI, we present examples of the effects of the latter in both the short and long term. The results show that GFDI has an important beneficial impact on the environment for early-stage investments in the short term. Notably, our findings indicate that GFDI’s long-term effects are more likely to be favourable. Furthermore, we analyze interactions between variables representing institutional quality and the impact of GFDI on EI. Our findings suggest that the positive effects of GFDI may be greater in nations with highly developed institutional systems.